1993
DOI: 10.1073/pnas.90.24.11623
|View full text |Cite
|
Sign up to set email alerts
|

The mdm-2 gene is induced in response to UV light in a p53-dependent manner.

Abstract: Irradiation of mammalian cells with UV light results in a dose-dependent accumulation of the p53 tumorsuppressor gene product that is evident within 2 hr. UV treatment causes a dramatic increase in p53-specific transcriptional transactivation activity and an increase in expression of the p53-responsive gene mdm-2. UV-stimulated mdm-2 expression is not directy correlated with the level of p53 protein in a cell because mdm-2 induction is delayed at high UV doses even though p53 levels rise almost immediately. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
173
1
2

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(184 citation statements)
references
References 18 publications
8
173
1
2
Order By: Relevance
“…MCL1) and death-promoting molecules (e.g. BAX), cells exposed to IR exhibit an upregulation of both p53 and MDM2, the latter being a negative regulator of p53 Chen et al, 1994;Finlay, 1993;Momand et al, 1992;Oliner et al, 1992;Perry et al, 1993;Wu et al, 1993;Xiong et al, 1993). In this case, it has been postulated that MDM2 might serve as part of a feedback loop, limiting the duration of growth-arrest by p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCL1) and death-promoting molecules (e.g. BAX), cells exposed to IR exhibit an upregulation of both p53 and MDM2, the latter being a negative regulator of p53 Chen et al, 1994;Finlay, 1993;Momand et al, 1992;Oliner et al, 1992;Perry et al, 1993;Wu et al, 1993;Xiong et al, 1993). In this case, it has been postulated that MDM2 might serve as part of a feedback loop, limiting the duration of growth-arrest by p53.…”
Section: Discussionmentioning
confidence: 99%
“…As expected from the involvement of p53 in this response, downstream targets of p53 appear to be involved (Kastan et al, 1992;Miyashita and Reed, 1995). These targets include GADD45, a growth-arrest and DNA damage-inducible gene, p21 CIP1/WAF1 , an inhibitor of cyclin-dependent kinases, and MDM2, a gene encoding a product that interacts with p53 (El-Deiry et al, 1993;Harper et al, 1993;Kastan et al, 1992;Miyashita and Reed, 1995;Noda et al, 1994;Perry et al, 1993;Zhan et al, 1994aZhan et al, ,b, 1995Selvakumaran et al, 1994;Miyashita et al, 1994). Gadd45 and p21 Cip1/Waf1 cause growth suppression and thus may serve as downstream e ectors of the growth-arrest response (Xiong et al, 1993;Zhan et al, 1994cZhan et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…After repair of DNA damage, accumulated Mdm2 rapidly degrades p53. See text for further details C127 cells to UV-C irradiation was investigated (Perry et al, 1993). The induction of Mdm2 by u.v.…”
Section: The P53-mdm2 Autoregulatory Feedback-loopmentioning
confidence: 99%
“…In a study by Perry and colleagues a large proportion of both Mdm2 and p53 seemed to be uncomplexed, which suggested that the ability of both proteins to interact with each other could e ectively be regulated (Perry et al, 1993). Complex formation was studied in more detail by Momand and Zambetti who found that Mdm2 was bound to a variable subpopulation of p53 in di erent cell types: all p53 was bound in 3T3DM cells while no detectable Mdm2 was bound in Balb/c3T3 cells or normal ®broblasts (Momand and Zambetti, 1996).…”
Section: The P53-mdm2 Autoregulatory Feedback-loopmentioning
confidence: 99%
“…p53 was found to function as a transcriptional regulator of several cellular genes: It transactivates genes like GADD45 (Kastan et al, 1992), p21 , MDM2 (Perry et al, 1993;Chen et al, 1994), bax (Miyashita and Reed, 1995) and cyclin G (Okamoto and Beach, 1994) and transrepresses TATAmediated transcription (Mack et al, 1993) of genes such as PCNA and several viral promoters Deb et al, 1992). Both, the expression and the activity of the p53 protein are tightly controlled.…”
Section: Introductionmentioning
confidence: 99%